Innovation Package and Scaling Readiness Assessment for Feed Pellet Production for Ruminants to Benefit Agro-pastoralists and Farmer Organizations in Tunisia - Rudiger, Udo (International Center for Agricultural Research in the Dry Areas, 2024)
This report presents a generated analysis of the outputs resulting from the implementation of the Scaling Readiness methodology to an innovation called feed pellet production for small ruminant in agropastoral contexts. Feed pellets are compressed local agro-industrial by products into nutrient dense livestock feed pellets. This innovation merits attention as it competes with costly and imported feed pellets or concentrates within the local market. The reports meticulously document the innovation and present the resulting sociotechnical innovation packages. These packages are indispensable for the successful and scalable implementation of the feed pelleting technique.